3n+7=((n-1)/2)

Simple and best practice solution for 3n+7=((n-1)/2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n+7=((n-1)/2) equation:



3n+7=((n-1)/2)
We move all terms to the left:
3n+7-(((n-1)/2))=0
We multiply all the terms by the denominator
3n*2))-(((n-1)+7*2))=0
We add all the numbers together, and all the variables
3n*2))-(((n-1)=0
Wy multiply elements
6n^2=0
a = 6; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·6·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$n=\frac{-b}{2a}=\frac{0}{12}=0$

See similar equations:

| 7w-5=180 | | 5x-2x+7-x=x+ | | 2-7p=-5p-7+5 | | (x+10)+5=59 | | 3+4+4•15=a | | 3q+4=180 | | 4.82x+24.1=48.2 | | 2.34(.01219-x)=x | | -2(m+7)=3(m-5)-4m | | 7p+3=180 | | 8v+10=11v+10 | | 3n+7=(n-1)/2 | | 8q-6=180 | | 14x+8=90 | | 7x+1=3x-14 | | (x+30)+36+90=180 | | 6-2g=10+6g | | 354=4x-x+x^2 | | 7x+9=2x+49 | | 5f+7=f+13 | | 4(x+3)-5(2x-1)=2-x | | 5x=3=2x-3 | | -15=4x-6x+1 | | -3y+6=42 | | -5=2w+9 | | 16x-3-4x=0 | | -6-5x-6x=82 | | n-72=3 | | 4(4m-3)-m-5)=-52 | | -8x+12=4x-36 | | 19x+7=3x+9 | | R=176-0.8a |

Equations solver categories